Feminism in Politics: The Most Significant Movement and Ideology - Ence Sopyan; Dwi Santoso (CV. Tripe Konsultan, 2025)
Feminism in politics is a movement and ideology focused on the struggle to achieve gender equality and enhance women's participation and representation in the political sphere. This study examined the role of feminism as a political ideology in driving global policy changes related to gender equality and women's representation. The participants in the study include a review of literature covering feminist movements in both developed and developing countries, such as the United States, France, India, and several African nations. A qualitative approach was adopted, utilising data collection methods such as literature analysis, with data analysed through thematic content analysis techniques. The findings reveal that feminism has significantly influenced gender equality policies, particularly in terms of women's representation in governmental institutions and policies aimed at protecting women from gender-based violence. Digital feminism, through campaigns such as #MeToo and #TimesUp, has accelerated the adoption of more inclusive policies. The study concludes that feminism plays a vital role in shaping inclusive and representative political policies, although challenges from conservative groups persist. The implications of this research include the importance of cross-cultural understanding in implementing gender equality policies globally.